Experimental Study on Calcium Hydroxide-Assisted Delignification of Hydrothermally Treated Sweet Sorghum Bagasse. (2nd September 2014) - Kudakasseril Kurian, Jiby; Gariepy, Yvan; Lefsrud, Mark; Orsat, Valerie; Seguin, Philippe; Yaylayan, Varoujan; Raghavan, G. S. Vijaya
Abstract : The hydrothermally treated sweet sorghum bagasse (SSB) powder was treated using Ca(OH)2 to extract the lignin from it. Changes in chemical composition of SSB and the formation of sugars and hydrolytic products were studied. The optimum conditions of 10% (g/g substrate) Ca(OH)2 and 106.3 min of isothermal treatment residence time at 394 K resulted in 69.67 ± 1.26% of the lignin extracted from the hydrothermally treated SSB powder, producing a solid residue containing 68.29 ± 0.31% residual cellulose and 13.26 ± 0.32% residual lignin in it. The Ca(OH)2 concentration and isothermal treatment residence time were significant in the responses observed. Treatment using Ca(OH)2 is one of the potential processes for the on-farm processing of lignocellulosic materials.